2022
DOI: 10.3390/bs12050145
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Relationship between Interpersonal Trust and Innovative Behavior: The Mediating Effects of Affective Organizational Commitment and Knowledge-Sharing

Abstract: The innovative behavior of employees is the micro-foundation of enterprise innovation. The objective of this study was to assess the role of gender differences in the effect of interpersonal trust on employee innovation and the mediating roles of organizational commitment and knowledge-sharing. This study tested research hypotheses with a multi-group structural equation model, using data collected from 688 participants in Shanghai, China. The results showed that interpersonal trust had significant impacts on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 59 publications
2
12
0
Order By: Relevance
“…Therefore, affective organizational commitment (i.e., an attitude of organizational dedication via voluntary motivation) may work as an intermediating mechanism that more clearly explains the relationship between core self-evaluation and innovative work behavior. In this regard, previous studies revealed the relationships between core selfevaluation and affective organizational commitment (Cadiz, 2010;Joo et al, 2012;Kittinger et al, 2020) and between affective organizational commitment and innovative work behavior (Ng et al, 2010;Nazir et al, 2018;Battistelli et al, 2019;Yuan and Ma, 2022), respectively. However, those empirical evidence cannot verify the mediating role of affective organizational commitment on the relationship between core self-evaluation and innovative work behavior because the three factors have not been analyzed in an identical research model based on a sound theoretical framework.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Therefore, affective organizational commitment (i.e., an attitude of organizational dedication via voluntary motivation) may work as an intermediating mechanism that more clearly explains the relationship between core self-evaluation and innovative work behavior. In this regard, previous studies revealed the relationships between core selfevaluation and affective organizational commitment (Cadiz, 2010;Joo et al, 2012;Kittinger et al, 2020) and between affective organizational commitment and innovative work behavior (Ng et al, 2010;Nazir et al, 2018;Battistelli et al, 2019;Yuan and Ma, 2022), respectively. However, those empirical evidence cannot verify the mediating role of affective organizational commitment on the relationship between core self-evaluation and innovative work behavior because the three factors have not been analyzed in an identical research model based on a sound theoretical framework.…”
Section: Introductionmentioning
confidence: 89%
“…According to the trait activation theory, organizational learning capacity (i.e., an organizational environment that promotes organizational learning) may act as a moderator on the relationship between core self-evaluation and innovative work behavior. In previous studies (Wang and Ellinger, 2011;Park et al, 2014;Gozukara et al, 2016;Lin and Lee, 2017;Türk and Biçer, 2018;Sari and Palupiningdyah, 2020;Yuan and Ma, 2022), organizational learning capacity was found to contributes to innovative work behavior by promoting the development of creative ideas and various social interactions. Additionally, Aboobaker and Zakkariya (2021) found that organizational learning capacity was a significant moderating variable in the relationship between personal characteristics, including digital learning orientation and readiness for change, and innovative work behavior.…”
Section: Introductionmentioning
confidence: 91%
“…The current corpus of research on corporate entrepreneurship acknowledges the crucial part played by bottom-up employee initiatives in bettering organizational circumstances and developing solutions (Rafique et al, 2021). Although innovative behavior and access to corporate archives are not usually prerequisites for entrepreneurship, they are still valuable building stones (Yuan & Ma, 2022).…”
Section: H1mentioning
confidence: 99%
“…Healthcare organizations are a sort of knowledge-intensive organizations, which involves many clinicians with expertise in different specialities. Their continuous updating of knowledge and technology is the embodiment and requirement of professionalism, which is crucial for patient care, the quality of health services, and the reduction of medical errors ( Gider et al, 2015 ; Yuan and Ma, 2022 ).By promoting the diffusion of health technology within and between organizations, knowledge sharing of appropriate health technology is commonly recognized as an efficient and effective way for health institutions to gain competitive advantages and improve performance ( Jackson et al, 2006 ; Wu et al, 2021 ). And it also has been playing a crucial role in strengthening the capacity of health service delivery and subsequently benefiting the overall health of national citizens.…”
Section: Introductionmentioning
confidence: 99%
“…Factors that influence knowledge sharing include individual demographic attributes, interpersonal relationships, and personality traits. Demographic characteristics mainly include gender, social status, work department and workplace ownership attributes ( Lee and Hong, 2014 ; Tausczik and Huang, 2020 ; Yuan and Ma, 2022 ). Studies on physician groups proved that differences in hospital ownership status, gender, age, position and departments led to barriers in knowledge sharing process, overload of work and negative attitude of senior physicians towards knowledge sharing ( Huang, 2014 ; Gider et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%